2009
DOI: 10.1063/1.3251366
|View full text |Cite
|
Sign up to set email alerts
|

Optical Thomson scatter from a laser-ablated magnesium plume

Abstract: We have carried out an optical Thomson scatter study of a KrF laser-ablated Mg plume. The evolution of the electron temperature and density at distances 2 -5 mm from the target surface has been studied. We have observed that the electron density falls more rapidly than the atomic density and believe that this is a result of rapid dielectronic recombination. A comparison of the electron density profile and evolution with simple hydrodynamic modeling indicates that there is a strong absorption of the laser in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
37
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 39 publications
7
37
0
1
Order By: Relevance
“…Analyses of the data at different times up to 1 µs and distances 2-5 mm from the target surface indicate much lower 0093-3813/$26.00 © 2011 IEEE electron density and temperature than in the case of KrF ablation under the same conditions [1]. Also, the decay of the electron density with time indicates a much smaller role for dielectronic recombination than that for the KrF case.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Analyses of the data at different times up to 1 µs and distances 2-5 mm from the target surface indicate much lower 0093-3813/$26.00 © 2011 IEEE electron density and temperature than in the case of KrF ablation under the same conditions [1]. Also, the decay of the electron density with time indicates a much smaller role for dielectronic recombination than that for the KrF case.…”
mentioning
confidence: 89%
“…In the attempt of better understanding the structure and expansion behavior of low-temperature laser-ablated plasmas, a wide range of diagnostic techniques, such as emission spectroscopy, LIF, Langmuir probes, and particle measurements, have been used. We have recently added Thomson scattering to this list [1], [3].…”
mentioning
confidence: 98%
“…Recently, we have added to this diagnostic capability by employing Thomson scattering (Delserieys et al, 2008a(Delserieys et al, , 2009). This is a powerful technique that has been widely used in fusion plasmas as well as high temperature laserplasmas, and electrically driven RF plasmas and more recently, as a proposed method for production of short X-ray bursts (e.g., Liu et al, 2010, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from early preliminary work (George et al, 1970;Izawa et al, 1968Izawa et al, , 1969, it has not been used very extensively in low temperature plumes of the sort investigated here. In previous work (Delserieys et al, 2008a(Delserieys et al, , 2009), we used KrF laser radiation to generate the plume. Our principal findings were that an isothermal model of expansion fitted the data better than an isentropic model (Delserieys et al, 2009;Stapleton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Optical emission spectroscopy has been successfully used previously for determining temperatures, species densities, and electrical conductivities of laser, [19][20][21][22] electrical arc 16,[23][24][25] and hybrid welding plasmas and has been used for the study of hybrid welding reported here. Previous research in hybrid welding [26][27][28][29] has indicated the two most important variables that significantly affect weld bead porosity, weld geometry and plasma light emission are the heat source separation distance and the arc current.…”
mentioning
confidence: 99%